2019
DOI: 10.1016/j.ptsp.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of limb dominance on change of direction biomechanics: A systematic review of its importance for injury risk

Abstract: Objective: To critically evaluate the effect of limb dominance on change of direction (COD) biomechanics associated with increased ACL injury-risk. Methods: A systematic review of the literature was conducted using Medline and Sport DISCUS databases. Studies that compared COD biomechanics (lower-limb/whole-body kinetics/kinematics) between limbs, contained an approach run, and included physically active participants were included. Results: Of the 456 articles identified, six were included. All studies investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 141 publications
1
42
0
1
Order By: Relevance
“…In accordance with the methods of Dos’Santos et al [ 45 ] and Brown et al [ 46 ], assessment of methodological quality was conducted on the 23 studies deemed eligible for inclusion in this review and is presented in Table 1 . Of the 23 studies, the mean methodological quality score was 11.86 (66%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with the methods of Dos’Santos et al [ 45 ] and Brown et al [ 46 ], assessment of methodological quality was conducted on the 23 studies deemed eligible for inclusion in this review and is presented in Table 1 . Of the 23 studies, the mean methodological quality score was 11.86 (66%).…”
Section: Resultsmentioning
confidence: 99%
“…An assessment of study quality was conducted as per previously established methods [ 45 , 46 ] using the modified scale constructed by Brown et al [ 46 ]. This is deemed to be more suitable for assessing the methodological quality of COD studies due to the omission of criteria such as random allocation, assessor blinding and subject blinding that are present in more commonly used scales such as the Cochrane or Delphi, Physiotherapy, Evidence Database scales.…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded that leg dominance could affect COD ability among young soccer players. However, considering leg dominance (i.e., kicking limb) instead of preferred direction (e.g., turning toward left or right) may lead to misinterpretations of potential bilateral differences because athletes do not necessarily perform faster COD with the kicking limb (Dos'Santos et al, 2019a;Dos'Santos et al, 2017). Moreover, no comparison was made between the COD deficit and total time (Dos'Santos et al, 2019a;Dos'Santos et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Soccer is a single-leg-dominant sport, which often exacerbates the use of a specific body side or a preferred path to change direction, especially in young players ( Rouissi et al, 2016a ; Rouissi et al, 2016b ). The presence of such a bilateral difference in young players reflects the presence of an asymmetry that should be quantified from both performance and injury risk perspectives ( Dos’Santos et al, 2019a ; Hart et al, 2014 ). Indeed, an inability to move efficiently in one direction as opposed to another could impede a player’s movement and performance within the pitch.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies equal a subject’s kicking leg with his/her dominant leg [ 49 – 51 ]. However, often this is not necessarily equivalent to the stronger or more skillful leg [ 52 ]. Also, in sports with repetitive and alternating movements, e.g., running or cycling, bilateral asymmetries are apparent [ 17 ].…”
Section: Discussionmentioning
confidence: 99%